Enhanced solar steam generation using carbon nanotube membrane distillation device with heat localization. (25th February 2019) - Miao, En-Dong; Ye, Meng-Qi; Guo, Cheng-Long; Liang, Lin; Liu, Qi; Rao, Zhong-Hao
Graphical abstract: Highlights: Carbon nanotube membrane was prepared for solar harvesting. Aerogel blanket was used as thermal insulator for heat localization. A membrane distillation device was designed and assembled. Thermal conversion efficiency up to 84.6% was achieved. Superior cyclic stability was demonstrated by a 10-cycle test. Abstract: High-efficiency solar steam generation through interfacial solar heating of the membrane is a promising approach to alleviate the shortage of freshwater resources. In this work, we developed a membrane distillation device (MDD), consisting of a carbon nanotube (CNT) membrane as solar absorption layer, a qualitative filter paper as water transmission pipeline and an aerogel blanket as thermal insulator to achieve efficient solar harvesting and heat localization for enhancing water evaporation. The results illustrated that the MDD achieved a thermal conversion efficiency of up to 84.6% at a light intensity of 1 kW m −2 and showed superior cyclic stability for 10 cycles test. As a consequence, the self-assembled and reusable MDD was suitable as a promising candidate for seawater desalination.